2002
DOI: 10.1016/s0140-6736(02)07946-1
|View full text |Cite
|
Sign up to set email alerts
|

Arteriovenous malformations

Abstract: Arteriovenous malformations of the brain are congenital vascular lesions that affect 0.01-0.50% of the population, and are generally present in patients aged 20-40 years. The usual clinical presentations are haemorrhage, seizures, progressive neurological deficit, or headache. Results of natural history studies have shown a yearly haemorrhage rate of 1-4%. Frequency of rebleeding has increased over the years, and several factors that increase risk of haemorrhage have been identified. Although substantial, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
232
2
6

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 371 publications
(255 citation statements)
references
References 113 publications
11
232
2
6
Order By: Relevance
“…9 History of hemorrhage, high blood pressure, intranidal aneurysm, venous stenosis, and deep venous drainage are the main factors that increase the likelihood of AVM rupture. 4,10,11 Although there are several therapeutic options to eradicate AVMs, the treatment-related morbidity is significant, especially for large, deep-seated, or eloquently located nidi. 6 The recently published ARUBA trial (A Randomized trial of Unruptured Brain Arteriovenous malformations) showed that medical management alone is superior to medical management with interventional therapy for the prevention of death or stroke in patients with unruptured brain AVMs.…”
Section: Introductionmentioning
confidence: 99%
“…9 History of hemorrhage, high blood pressure, intranidal aneurysm, venous stenosis, and deep venous drainage are the main factors that increase the likelihood of AVM rupture. 4,10,11 Although there are several therapeutic options to eradicate AVMs, the treatment-related morbidity is significant, especially for large, deep-seated, or eloquently located nidi. 6 The recently published ARUBA trial (A Randomized trial of Unruptured Brain Arteriovenous malformations) showed that medical management alone is superior to medical management with interventional therapy for the prevention of death or stroke in patients with unruptured brain AVMs.…”
Section: Introductionmentioning
confidence: 99%
“…This vascular malformation is thought to be congenital, and develops before or after birth [2] from a residual of the primitive artery-vein connection. Its most common symptom is intracranial hemorrhage with an estimated risk of 1.3-3.9% yearly after the diagnosis of AVM [3].…”
Section: Introductionmentioning
confidence: 99%
“…Other signs may include intractable seizures, headache and ischemic steal syndrome. The prevalence of AVM is estimated to be approximately 0.01% and the detection rate ranges between 1.12-1.34 per 100 000 person years [1,2]. Although most cases of AVM are sporadic, a total of 53 patients from 25 families have been reported [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, the nature of VEGF-induced angiogenesis in the normal adult brain is unknown. A fundamental question that remains to be resolved in understanding the pathobiology of BAVM is whether the regional nature of vascular malformations is germline, such as HHT or venous malformations (Vikkula et al, 1996), or sporadic in nature, such as sporadic BAVM (Arteriovenous Malformation Study Group, 1999;Fleetwood and Steinberg, 2002). It is possible that some subclinical event might locally alter the balance of vascular signaling, such as minor trauma or ischemia in a subject with a genetic predispostion to have altered angiogenic responses.…”
mentioning
confidence: 99%